The influence of biological rhythms on host–parasite interactions. (June 2015) - Martinez-Bakker, Micaela; Helm, Barbara
Highlights: The immune system of mammals and birds displays circadian and annual rhythms. Parasites display rhythms in reproduction within, and in release from, their hosts. The rhythms are synchronised to and modulated by environmental factors. Host and parasite rhythms can impose temporal structure on epidemiological dynamics. Host and parasite rhythms might generate an arms race in the temporal domain. Abstract : Biological rhythms, from circadian control of cellular processes to annual cycles in life history, are a main structural element of biology. Biological rhythms are considered adaptive because they enable organisms to partition activities to cope with, and take advantage of, predictable fluctuations in environmental conditions. A flourishing area of immunology is uncovering rhythms in the immune system of animals, including humans. Given the temporal structure of immunity, and rhythms in parasite activity and disease incidence, we propose that the intersection of chronobiology, disease ecology, and evolutionary biology holds the key to understanding host–parasite interactions. Here, we review host–parasite interactions while explicitly considering biological rhythms, and propose that rhythms: influence within-host infection dynamics and transmission between hosts, might account for diel and annual periodicity in host–parasite systems, and can lead to a host–parasite arms race in the temporal domain.